Candidate therapeutic agents in a newly established triple wild‐type mucosal melanoma cell line. Issue 7 (4th June 2022) - Shi, Chaoji; Gu, Ziyue; Xu, Shengming; Ju, Houyu; Wu, Yunteng; Han, Yong; Li, Jiayi; Li, Chuwen; Wu, Jing; Wang, Lizhen; Li, Jiang; Zhou, Guoyu; et al.
Abstract: Background: Mucosal melanoma has characteristically distinct genetic features and typically poor prognosis. The lack of representative mucosal melanoma models, especially cell lines, has hindered translational research on this melanoma subtype. In this study, we aimed to establish and provide the biological properties, genomic features and the pharmacological profiles of a mucosal melanoma cell line that would contribute to the understanding and treatment optimization of molecularly‐defined mucosal melanoma subtype. Methods: The sample was collected from a 67‐year‐old mucosal melanoma patient and processed into pieces for the establishment of cell line and patient‐derived xenograft (PDX) model. The proliferation and tumorigenic property of cancer cells from different passages were evaluated, and whole‐genome sequencing (WGS) was performed on the original tumor, PDX, established cell line, and the matched blood to confirm the establishment and define the genomic features of this cell line. AmpliconArchitect was conducted to depict the architecture of amplified regions detected by WGS. High‐throughput drug screening (HTDS) assay including a total of 103 therapeutic agents was implemented on the established cell line, and selected candidate agents were validated in the corresponding PDX model. Results: A mucosal melanoma cell line, MM9H‐1, was established which exhibited robust proliferation and tumorigenicity after more than 100 serial passages. Genomic analysis of MM9H‐1, corresponding PDX, and the original tumor showed genetic fidelity across genomes, and MM9H‐1 was defined as a triple wild‐type (TWT) melanoma subtype lacking well‐characterized "driver mutations". Instead, the amplification of several oncogenes, telomerase reverse transcriptase (TERT), v‐Raf murine sarcoma viral oncogene homolog B1 (BRAF), melanocyte Inducing transcription factor (MITF) and INO80 complex ATPase subunit (INO80), via large‐scale genomic rearrangement potentially contributed to oncogenesis of MM9H‐1. Moreover, HTDS identified proteasome inhibitors, especially bortezomib, as promising therapeutic candidates for MM9H‐1, which was verified in the corresponding PDX model in vivo. Conclusions: We established and characterized a new mucosal melanoma cell line, MM9H‐1, and defined this cell line as a TWT melanoma subtype lacking well‐characterized "driver mutations". The MM9H‐1 cell line could be adopted as a unique model for the preclinical investigation of mucosal melanoma.